Modelling knowledge transfer of nursing students during clinical placement / Nor Azairiah Fatimah Othman - Othman, Nor Azairiah Fatimah (Institute of Graduate Studies, UiTM, 2017)
The current study explored factors affecting behavioral of knowledge transfer and the antecedents predicting this within the Theory of Planned Behavior (TPB) framework. This study made an attempt to incorporate knowledge transfer-related variables (articulability of knowledge, credibility of knowledge source, gap of theory-practice, embedded knowledge and environmental uncertainty) into the framework. The premise of the model is to provide guideline of necessary conditions that are influential to knowledge transfer behavior in the clinical placement. It is hoped that by holistically understanding and paying closer attention to these predictors, a more comprehensive strategy can be devise beforehand to alleviate any problems that might negatively hinder activities of acquiring and applying new knowledge at the point of clinical placement, which subsequently maximize required clinical experience and in turn increase the levels of clinical competence. The posited model was validated quantitatively using field surveys to one of key stakeholders of clinical placement; the nursing students. The influence of the variables selected for this study was tested on two distinct samples of Lower Semester Group, LSG (semester 1- 3) and Higher Semester Group, HSG (semester 4-6) separately… The assessment and improvement of angle stability condition of the power system using particle swarm optimization (PSO) technique / Nor Azwan Mohamed Kamari This thesis presents the assessment and improvement of stability domains for the angle stability condition of the power system using particle swarm optimization (PSO) technique. An efficient optimization method using PSO for synchronizing torque coefficients Ks and damping torque coefficients Kd to solve angle stability problems was developed and used to identify the angle stability condition on single and multi machine system. In order to accelerate the determination of angle stability, particle swarm optimization (PSO) is proposed to be implemented in this study. The application of the proposed algorithm has been justified as the most accurate with lower computation time as compared to other optimization techniques such as evolutionary programming (EP) and artificial immune system (AIS). Subsequently, a newly control technique named as proportional-integral-derivative (PID) incorporated with flexible AC transmission (FACTS) device is proposed in this study to improve the damping capability of the system. The minimum damping ratio ξmin was applied as an indicator to precisely determine the angle stability condition based on PSO technique. The proposed optimization technique was compared with respect to EP and AIS…